Effect of probiotics supplementations on health status of athletes - Bhagavathi Sundaram Sivamaruthi (2020)
© 2019 by the authors. Licensee MDPI, Basel, Switzerland. Athletes are prone to several health complications, including upper respiratory tract infections, allergies, and gastrointestinal discomforts during practice and after the performance due to the intense exercise, travel, insufficient rest and restricted food consumption. Probiotics are well known as complementary therapeutic and health supplements for several diseases and disorders. Studies suggest that the intervention of probiotics improved the health status of elite athletes, but the results are not consistent in all the studies. The beneficial effect of probiotic supplementation profoundly relies on species or strain, dose, duration, form, and host physiology. The manuscript summarizes the effect of probiotic supplementation on health status of athletes. The literature was collected from PubMed, Scopus, Web of Science, and Google Scholar using the search term “probiotic and athletes”. As per the literature survey, probiotic supplementation improved the intestinal permeability, immune system, intestinal microbiota, inflammatory system, reduced the severity and incidence of respiratory tract infections, and duration of gastrointestinal symptoms. Several studies were conducted on Lactobacillus species and the outcomes were found to be species-or strain-specific. More studies are required to know the detailed mechanism behind the beneficial effect of probiotic intervention in athletes. Further studies are desired on formulation and optimization of probiotic supplements to develop generalized and personalized sports supplements to boost the overall health and enactment of elite athletes.